Nudging the obese: a UK–US consideration. Issue 3 (23rd April 2014) - Oliver, Adam; Ubel, Peter
Abstract Over recent years, nudge policies have become increasingly popular (if somewhat confused) internationally. This article attempts to clarify what a nudge entails, and critically summarises some of the nudge policies that have been proposed to motivate weight loss in the United Kingdom and the United States. Despite the fact that most of the evidence on nudge-related policy has so far been produced in the United States, and that the leading nudge champions are American, the United Kingdom, at least with respect to considering policy interventions of this kind at the national level, appears to be relatively advanced. That said, nudge interventions remain of marginal practical import everywhere, and are never going to solve completely the obesity problem. Nonetheless, even a marginal effect may extend and improve many lives, a result that would satisfy most behavioural economists.